Current research in early Mesopotamian studies workshop organized at the 65th Rencontre Assyriologique Internationale, Paris 2019 - Current Research in Early Mesopotamian Studies 2019 Paris; Bramanti, Armando 1989-; Kraus, Nicholas ca. 20./21. Jh.; Notizia, Palmiro 1980-; Rencontre assyriologique internationale 2019 Paris (Münster Zaphon, 2021)
Intro -- Table of Contents -- Preface -- Program of the Workshop -- Bramanti / Kraus / Notizia: Early Mesopotamia in the Third Millennium CE: The Last Two Decades of Research (2000-2020) -- Kelley: More Than a Woman? On Proto-cuneiform SAL and the Archaic "Tribute List" -- Wang: How Many Priest-Kings in Town? A Glance at the Political Structure of the City of Uruk at the Dawn of Civilization -- Benati / Lecompte: The Scale and Extent of Political Institutions in Early Dynastic Mesopotamia: The Case of Archaic Ur -- Rudik: Herumtreibende Kinder, bewaffnete Kälber und Götter in Aufr uhr: Die frühdynastischen Beschwörungen aus CUSAS 32 -- Archi: Ebla(itologists) and Sumer(ologists): Reasons for a Dialogue -- Bonechi / Winters: Ebla through Huwawa's Gaze: Inner and Outer Perspectives on Early Syria, between Mesopotamia, Egypt, and Anatolia -- Kraus: An Addition to the Early Dynastic Lexical Tradition: Early Dynastic Personal Names A (Word List Z) -- Bramanti: The Making of a Sign List: Toward a Paleography of Early Dynastic Umma -- Postgate: More Points of Grammar in Gudea: Resuscitating the Dynamic Mode -- Indexes.
"The present volume brings together articles concerned with diverse aspects of the Early Mesopotamian documentation - i.e. texts dating to the Archaic, Early Dynastic (ED I-II, IIIa, IIIb), Sargonic, and Gutian periods, and extending geographically to include Ebla and its royal archives. Early Mesopotamia has recently attracted the attention of Assyriologists thanks to the enormous amount of new epigraphic material - mostly clay tablets - which appeared in the last decades. As a result of the sudden publication of thousands of texts, the Archaic, Early Dynastic, Sargonic, and post-Sargonic periods have assumed new relevance in the general landscape of research on third millennium Mesopotamia, which was until recently dominated by the Neo-Sumerian studies. Among others J. N. Postgate re-investigates the Dynamic Mode of Gudea's Sumerian; N. Rudik continues her studies on Early Dynastic incantations from the Schøyen collection; G. Benati & C. Lecompte take into consideration the political institutions in Early Dynastic Ur and X. Wang those of the city of Uruk. The volume is supplemented by extensive indices." -- From publisher's website
Description based on publisher supplied metadata and other sources
Beiträge teilweise englisch, teilweise deusch
Keywords: To 634; Assyriology -- Congresses; Electronic books; Assyriologie - Congrès; Antiquities; Assyriology; Civilization; Assyriology - Congresses; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings; Actes de congrès; Iraq -- Civilization -- To 634 -- Congresses; Iraq -- Antiquities -- Congresses; Irak - Civilisation - Jusqu'à 634 - Congrès; Irak - Antiquités - Congrès; Iraq; Iraq - Civilization - To 634 - Congresses; Iraq - Antiquities - Congresses; Mesopotamia - History - Congresses; Mesopotamia - Civilization - Congresses; Mesopotamia (region); Konferenzschrift